2005
DOI: 10.1111/j.1468-2389.2005.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Better Late than Never? The Relationship between Ratings of Attendance, Punctuality, and Overall Job Performance among Nursing Home Employees

Abstract: This study examined the relationship between lateness, absenteeism, and overall job performance among nursing home employees. We addressed four issues: (a) agreement between subordinate and superior in their ratings, (b) the stability of rated lateness and rated absenteeism over 6 months, (c) the correlation between ratings of lateness and absenteeism assigned by the worker to himself or herself and the corresponding ratings from supervisors, and (d) the relationship of rated lateness and rated absenteeism to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…neglect (Barling et al, 2001), and both partial and full absence (Roszkowski et al, 2005) with work performance. Finally, two research questions might be pursued to enhance the external validity of the models presented here.…”
Section: Study Limitations and Directions For Future Researchmentioning
confidence: 99%
“…neglect (Barling et al, 2001), and both partial and full absence (Roszkowski et al, 2005) with work performance. Finally, two research questions might be pursued to enhance the external validity of the models presented here.…”
Section: Study Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Lateness likely elicits Black–White and Hispanic–White differences in performance evaluations, which in turn translates into differential opportunities for advancement. Research showed that lateness is related to supervisor ratings of subordinates' performance (Roszkowski et al ., ); yet, ‘lateness–performance studies in the literature are rare’ (Koslowsky et al ., , p. 80) and ‘heterogeneity of the observed correlations may also be attributed to moderators’ (Koslowsky et al ., , p. 84). Accordingly, stereotypes may beget differential explanation of lateness behaviour, resulting in more negative performance appraisal for Black people and Hispanics who are tardy than for Whites exhibiting similar behaviour.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Managers make promotion decisions based on the results of their subordinates' performance appraisal to avoid legal repercussions and promote workplace equality (Castilla & Benard, ; Greenhaus, Parasuraman, & Wormley, ; Kleiman & Durham, ; Lyness & Heilman, ). Although the effects of task and contextual performance on the ratings of overall performance are well documented (Arvey & Murphy, ; Podsakoff, Whiting, Podsakoff, & Blume, ; Rotundo & Sackett, ), the impact of employee lateness behaviour (i.e., showing up for work after scheduled work time; Johns, ) within the same domain remains understudied (Roszkowski et al ., ). Clearly, being late is not socially or organizationally valued behaviour, and thus, one would expect excessive tardiness to have a negative influence on performance appraisal and subsequent advancement.…”
Section: Introductionmentioning
confidence: 97%
“…In his interesting publication on punctuality, attendance policy and organizational performance Thierry (2018, p.20) quoting Professor Emeritus Don Marquis (Professor of Philosophy at the University of Kansas) stated that, "Punctuality is one of the cardinal business virtues: always insist on it in your subordinates". Interestingly, Roszkowski et al (2005) in an exciting study titled, "Better Late than Never? The relationship between ratings of attendance, punctuality, and overall job performance among Nursing Home Employees", concluded that, punctuality was more highly correlated with impressions of overall job performance from the perspective of the worker as well as the supervisor, even when restriction in range was considered as compared to attendance (p.218).…”
Section: Employee Punctualitymentioning
confidence: 99%